Porcine deltacoronavirus (PDCoV) modulates calcium influx to favor viral replication - Bai, Dongcheng (Virology, 2020)
Ionic calcium (Ca(2+)) is a versatile intracellular second messenger that plays important roles in cellular physiological and pathological processes. Porcine deltacoronavirus (PDCoV) is an emerging enteropathogenic coronavirus that causes serious vomiting and diarrhea in suckling piglets. In this study, the role of Ca(2+) to PDCoV infection was investigated. PDCoV infection was found to upregulate intracellular Ca(2+) concentrations of IPI-2I cells. Chelating extracellular Ca(2+) by EGTA inhibited PDCoV replication, and this inhibitory effect was overcome by replenishment with CaCl(2). Treatment with Ca(2+) channel blockers, particularly the L-type Ca(2+) channel blocker diltiazem hydrochloride, inhibited PDCoV infection significantly. Mechanistically, diltiazem hydrochloride reduces PDCoV infection by inhibiting the replication step of the viral replication cycle. Additionally, knockdown of CACNA1S, the L-type Ca(2+) voltage-gated channel subunit, inhibited PDCoV replication. The combined results demonstrate that PDCoV modulates calcium influx to favor its replication.